Applying agency theory and the resource-based view in explaining performance differences between family and non-family businesses - Duh, Mojca (Naše gospodarstvo, 2010)
This paper examines the applicability of different theoretical approaches in studying and explaining performance differences between family and non-family businesses. The main objective of the contribution is to analyse potential limitation of applied theories and make proposals regarding the implication of these theories in research on family business performance. We limit our research to agency theory and the resource-based view of the firm, which have recently received most of the attention in theoretical as well as empirical family business studies.
Keywords: zasebna podjetja; družinska podjetja; uspešnost; poslovna uspešnost; ekonomske teorije